Analisis Self Regulated Learning (SRL) Pada Pembelajaran Daring Mahasiswa Pendidikan Kimia Universitas Mataram - Thoyibah, Zurriyatun; Anwar, Yunita Arian Sani; Hadisaputra, Saprizal; Junaidi, Eka (FKIP University of Mataram, 2024)
This study aims to determine the level of Self Regulated Learning (SRL) in online learning for chemistry education students at the University of Mataram. This type of research is descriptive research with a quantitative approach. The sample used consisted of 200 active students of the chemistry education study program at the University of Mataram. Sampling was carried out using proportionated stratified random sampling. The instruments used in this study were student response questionnaires. The measurement scale used is the Likert scale, with alternative answers to questions consisting of 4 alternative answers and 25 statement items that include 5 indicators that have been tested for validity in the research instrument trial (test validity and reliability). The questionnaire was distributed online which was compiled into a google form and sent via WhatsApp. The analysis technique uses descriptive statistical analysis techniques. The results showed that the average value from the analysis of the overall indicators obtained the highest average value was indicator 5 (seeking help) which was 2,916 and the indicator with the lowest average value was indicator 3 (environmental structuring) with a value of 2,613. Based on these data, as many as 17 of 200 students have a poor level of Self Regulated Learning, 79 of 200 students have a Self Regulated Learning fairly good 92 out of 200 students have a good level of Self-Regulated Learning, then 12 out of 200 students have Self Regulated Learning in online learning. It can be concluded that the level of Self Regulated Learning (SRL) in online learning of chemistry education students at the University of Mataram is in the good category.